2020
DOI: 10.1140/epjp/s13360-020-00864-0
|View full text |Cite
|
Sign up to set email alerts
|

Electric vector potential formulation in electrostatics: analytical treatment of the gaped surface electrode

Abstract: Electric vector potential Θ(r) is a legitimate but rarely used tool to calculate the steady electric field in free-charge regions. Commonly, it is preferred to employ the scalar electric potential Φ(r) rather than Θ(r) in most of the electrostatic problems. However, the electric vector potential formulation can be a viable representation to study certain systems. One of them is the surface electrode SE, a planar finite region A− kept at a fixed electric potential with the rest grounded including a gap of thick… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
1
9
1
Order By: Relevance
“…Particularly, the three-dimensional vector field due to a circular-deformed loop with low symmetry. Analytic solutions of the BSL integrals are outstanding for solving steady electric, magnetic or fluid flow problems, as it has been demonstrated in [24,25] by the authors of the present study 3 .…”
Section: Velocitymentioning
confidence: 56%
See 2 more Smart Citations
“…Particularly, the three-dimensional vector field due to a circular-deformed loop with low symmetry. Analytic solutions of the BSL integrals are outstanding for solving steady electric, magnetic or fluid flow problems, as it has been demonstrated in [24,25] by the authors of the present study 3 .…”
Section: Velocitymentioning
confidence: 56%
“…3 For instance, the recent methodology in [25] demonstrates how the electric field of Gaped Surface Electrode systems can be obtained from the weighted average of their gapless counterparts. In that work, it was formally demonstrated that the electric field of the Gapped surface electrode with gap G is given by…”
Section: Vortex Filaments Magnetostaticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present article demonstrated another plausible approach to studying the gaped SE advantageous regarding Ref. (Salazar et al, 2020) since it becomes mathematically simpler. That is constructing the electric vector potential from a superposition of vector potentials † As presented in the reference, the time-dependent version of Eq.…”
Section: Discussionmentioning
confidence: 90%
“…As shown in Ref. (Salazar et al, 2020), one can obtain the Biot-Savart law without solving the Laplace's equation. That alternative derivation is by employing the Helmholtz decomposition and Green's theorems.…”
Section: Introductionmentioning
confidence: 99%